Chapter 9 Whydunnit? Causal Explanations in Sentencing Offenders With Mental Health Problems - Walvisch, Jamie (Taylor & Francis, 2024)
Emeritus Professor McSherry has written extensively on the intersection between criminal law and mental health. The concept of 'causation' is central to the way the law deals with mentally disordered offenders: the 'insanity' defence requires a causal connection between the offender's psychopathology and the offence; and mitigation at sentencing frequently relies on proof of a causal link. While 'causation' is a commonly used term, there is significant variation in the way that different disciplines understand its meaning. This is problematic, as explanations for offending that are proffered to the courts by mental health experts must function within a legal epistemological framework if they are to carry weight. This chapter considers how Australian, English and Welsh sentencing courts currently assess the causal relationship between mental disorders and offending, and the challenges that arise when sentencing courts rely on evidence from mental health experts. It draws on Nigel Walker's notion of 'possibility' explanations to present a framework for experts to provide robust explanations for offending that provide defensible opinions on the nature and strength of the causal relationship. It also considers the roles that legal practitioners and the courts should play in assessing the causal issue.